A Rare Case of Disseminated Tuberculosis of the Bone Marrow in Systemic Lupus Erythematosus: Case Report. Issue 18 (May 2016) - Chen, Dongying; Yang, Zheng; Yang, Ying; Zhan, Zhongping; Yang, Xiuyan
Abstract : Abstract: Patients with systemic lupus erythematosus (SLE) are susceptible to tuberculosis (TB), especially in endemic areas such as China. The variable and nonspecific clinical features of disseminated TB often leads to an erroneous or misdiagnosis. When a patient presents with TB of the bone marrow, the clinical condition is more perplexing and the prognosis is typically poor. Till now, there is no case report after apatinib came in the market. Here, we report a case of TB of the bone marrow accompanied with SLE. The patient exhibited remarkable features, including widespread lesions in the lungs, spinal vertebrae, sacrum, and ilium that were found to be consistent with TB of the bone marrow after histopathological examination. This case highlights the importance of clinical suspicion for TB during the follow-up of SLE patients, especially in endemic areas. An aggressive diagnostic biopsy should be performed in suspected TB patients as early as possible.